Groundwater potential assessment in Pino region, South Bengkulu, Indonesia using geo-investigation, remote sensing, and GIS approaches - Ashar Muda Lubis; Hera Wahyu Fauzi; Arya J. Akbar (Results in Earth Sciences)
Groundwater plays significant role in fulfilling the needs of local community in Indonesia. For example, in Pino region, South Bengkulu, Indonesia the people are experienced challenges in prospecting groundwater resources. Some locations provide enough groundwater, while some are not. Therefore, this study aims to investigate the distribution of groundwater potential in Pino region by using Geo-investigation Electrical Resistivity Tomography (2D ERT), Remote Sensing (RS), and Geographical Information System (GIS) methods. Various parameters related to groundwater potential were weighted with the Analytical Hierarchy Process (AHP) to generate a groundwater potential distribution map. In order to validate our results, we compared the distribution map with subsurface resistivity structures obtained from ERT data inversion. The distribution map of the groundwater potential derived by the RS and GIS methods is classified into five classes such low, fair, moderate, good, and excellent classes, respectively. In general, we found that majority of the research area is classified to fair and moderate classes of the groundwater potential. In the ERT results, low resistivity values of 0.13–7.60 Ω.•m are interpreted as subsurface aquifers at the depths of 3–50 m. The comparison of ERT results and the distribution map with AHP shows a good consistent of the groundwater potential. This study provides valuable insights for local authorities and local communities in the Pino region, South Bengkulu, Indonesia to plan and manage their groundwater resources more effectively.